PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT DAN NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Aneka Industri yang Terdaftar di BEI Tahun 2017-2019) - ,Al Azhar, Aldo Maalik , Poppy Nurmayanti M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine the effect of Enterprise risk management on firm value. This research is quantitative research. The population in this study were companies on the Indonesia Stock Exchange (IDX) in 2017-2019. The sample in this study is a Miscellaneous Industry Sector Manufacturing Company listed on the IDX for the 2017-2019 period and uses a non-probability sampling method with Purposive sampling technique where sampling is limited to those that can provide the desired information. The type of data used in this study is secondary data. The analysis method used is Multiple Regression Analysis using SPSS version 25.00. The statistical results in this study indicate that the ERM disclosure variable has an effect on firm value. Keywords:Enterprise Risk Management, Firm Value